Remote sensing of volcanic CO2, HF, HCl, SO2, and BrO in the downwind plume of Mt. Etna - Butz, André; Dinger, Anna Solvejg; Bobrowski, Nicole; Fieber, Lukas; Kuhn, Jonas; Lübcke, Peter; Tirpitz, Lukas (Atmospheric measurement techniques, 2017)
Remote sensing of the gaseous composition of non-eruptive, passively degassing volcanic plumes can be a tool to gain insight into volcano interior processes. Here, we report on a field study in September 2015 that demonstrates the feasibility of remotely measuring the volcanic enhancements of carbon dioxide (CO2), hydrogen fluoride (HF), hydrogen chloride (HCl), sulfur dioxide (SO2), and bromine monoxide (BrO) in the downwind plume of Mt. Etna using portable and rugged spectroscopic instrumentation. To this end, we operated the Fourier transform spectrometer EM27/SUN for the shortwave-infrared (SWIR) spectral range together with a co-mounted UV spectrometer on a mobile platform in direct-sun view at 5 to 10km distance from the summit craters. The 3 days reported here cover several plume traverses and a sunrise measurement. For all days, intra-plume HF, HCl, SO2, and BrO vertical column densities (VCDs) were reliably measured exceeding 5 × 1016, 2 × 1017, 5 × 1017, and 1 × 1014moleccm−2, with an estimated precision of 2.2 × 1015, 1.3 × 1016, 3.6 × 1016, and 1.3 × 1013moleccm−2, respectively. Given that CO2, unlike the other measured gases, has a large and well-mixed atmospheric background, derivation of volcanic CO2 VCD enhancements (ΔCO2) required compensating for changes in altitude of the observing platform and for background concentration variability. The first challenge was met by simultaneously measuring the overhead oxygen (O2) columns and assuming covariation of O2 and CO2 with altitude. The atmospheric CO2 background was found by identifying background soundings via the co-emitted volcanic gases. The inferred ΔCO2 occasionally exceeded 2 × 1019moleccm−2 with an estimated precision of 3.7 × 1018moleccm−2 given typical atmospheric background VCDs of 7 to 8 × 1021moleccm−2. While the correlations of ΔCO2 with the other measured volcanic gases confirm the detection of volcanic CO2 enhancements, correlations were found of variable significance (R2 ranging between 0.88 and 0.00). The intra-plume VCD ratios ΔCO2∕SO2, SO2∕HF, SO2∕HCl, and SO2∕BrO were in the range 7.1 to 35.4, 5.02 to 21.2, 1.54 to 3.43, and 2.9 × 103 to 12.5 × 103, respectively, showing pronounced day-to-day and intra-day variability.